The Implementation of Extended Examination Duration for Students With ADHD in Higher Education. Issue 14 (December 2019) - Jansen, Dorien; Petry, Katja; Evans, Steven W.; Noens, Ilse; Baeyens, Dieter
Objective: Recently, research indicated that extended examination duration was perceived as effective by students with ADHD. However, the objective effectiveness of this accommodation has not been researched extensively. This study addresses this gap in literature. Method: A total of 30 students with ADHD and 30 matched typically developing controls (TDC) participated in a simulation of a real-life examination. They filled in three parallel versions of a paper-and-pencil test in three time conditions: 1 hr (+0%), 1 hr 20 min (+33%), and 1 hr 30 min (+50%). Results: When granted extended examination duration, students with ADHD and TDC use extra time but their performance does not increase. In addition, test-taking strategies were altered to a limited extent, and strategies that are perceived as effective (e.g., marking key words) were rarely used by the students. Conclusion: It is concluded that extended examination duration is not objectively effective in an experimental design. Limitations and guidelines for future research are formulated.